Subjective Well-Being And Happiness Among Boarding School Students Experiencing Bullying In Aceh - Vera Nova; Izzatur Rayyan; Hidayatunnisa Aifan (Seurune : Jurnal Psikologi Unsyiah, 2025)
Bullying can occur anywhere and can be experienced by anyone, even at school. This condition affects students' subjective well-being and ultimately impacts their happiness during the learning process at school. This study aims to investigate the influence of subjective well-being on the happiness of boarding school students who are victims of bullying in Aceh. The respondents in this study consisted of 313 students from boarding schools in Aceh Besar and Banda Aceh. The measurement tools used were a modified version of the Subjective Well-Being Inventory (SUBI) and the Oxford Happiness Questionnaire. Data were analyzed using simple linear regression analysis, with a correlation coefficient (r) of 0.387 and a significance level of 0.000 (p0.05), indicating a positive relationship between subjective well-being and happiness. The higher the level of subjective well-being felt by students, the greater their happiness. Conversely, the lower the level of subjective well-being felt by students, the lower their happiness among boarding school students who are victims of bullying in Aceh. Further research needs to consider other psychosocial variables and cross-cultural perspectives to deepen our understanding of the role of subjective well-being in adolescent happiness.Abstrak: Bullying dapat terjadi di mana saja dan dapat dialami oleh siapa saja, bahkan di sekolah. Kondisi ini memengaruhi kesejahteraan subjektif siswa dan pada akhirnya berdampak pada kebahagiaan mereka selama proses pembelajaran di sekolah. Penelitian ini bertujuan untuk mengetahui pengaruh kesejahteraan subjektif terhadap kebahagiaan siswa sekolah asrama yang menjadi korban bullying di Aceh. Responden dalam penelitian ini terdiri dari 313 siswa dari sekolah asrama di Aceh Besar dan Banda Aceh. Alat ukur yang digunakan adalah versi modifikasi dari Inventori Kesejahteraan Subjektif (SUBI) dan Kuesioner Kebahagiaan Oxford. Data dianalisis menggunakan teknik analisis regresi linier sederhana, dengan nilai korelasi (r) sebesar 0,387 dan tingkat signifikansi sebesar 0,000 (p0,05) artinya terdapat pengaruh positif antara kesejahteraan subjektif dan kebahagiaan. Semakin tinggi tingkat kesejahteraan subjektif yang dirasakan oleh siswa, semakin besar kebahagiaan mereka. Sebaliknya, semakin rendah tingkat kesejahteraan subjektif yang dirasakan oleh siswa, semakin rendah pula kebahagiaan di antara siswa sekolah asrama yang menjadi korban bullying di Aceh. Penelitian selanjutnya perlu mempertimbangkan variabel psikososial lain serta perspektif lintas budaya untuk memperdalam pemahaman tentang peran subjective well-being terhadap kebahagiaan remaja.